Body, writing and performance: Performative education in initial teacher training in Arts (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Based on our practical experience, in this article we present two procedures for teaching Art exploring the relationships between body, writing and performance. By means of different methodological choices, we attempted to understand how two distinct pedagogical practices have configured ways of thinking on performance in Education, especially those capable of expanding our understanding of performative writing in teacher training in a Bachelor's Degree in Visual Arts and a Bachelor's Degree in Dance at a public university.
Keywords: body; perfomance; writing; performance writing; teacher training